Marketing Strategy and Product Development for Umroh Travel Services (Case Study: Umroh Bareng Yuk) (The Indonesian Journal of Business Administration, 2021)
Umroh Bareng Yuk (UBY) from PT. Sultanah Napisah Mandiri is a travel services provider which focuses on Islamic religious tour (Umrah and Hajj). UBY applied focused cost leadership for its services. Among the expensive umrah services from its competitor, UBY offers affordable umrah services to the customers without reducing the service level. However, this strategy is not generating good sales. UBY needs to evaluate its marketing strategy and product development in order to increase its value and revenue.The research is needed to analyze the effectiveness of UBY marketing strategy and gain new insights to compete in this industry. The data basis is collected by primary data collection and customer interview. SWOT, Resource-based model, Marketing Mix, STP, and Porter Five Forces analysis are used to analyze UBY’s strength and what it can offer to the market. The result of the research: UBY needs to emphasize on the promotional content in social media, improve the marketing and sales admins interaction and responses to customer, and improve physical evidence to increase customers trust. UBY will implement the improvement plan within 6 (six) months and will evaluate the result to determine further actions.Keywords: umrah service provider, travel business, marketing strategy.